Introduction - Iris Sportel (Oñati Socio-Legal Series)
The state is an important presence in the lives of many minority families. This special issue aims to investigate the interactions of minority families with law and state institutions from a socio-legal perspective, with a particular focus on issues relating to children. This introduction focuses on two observations. First of all, minority families tend to get into contact with law and state institutions relatively often. For migrant and transnational families, migration law can have a large and enduring impact on many aspects of their lives. Furthermore, marginalisation of minorities and differences in decision-making by state actors can contribute to an overrepresentation of minority families in state interventions such as the child protection or criminal justice systems. Secondly some minority families tend to avoid state law and institutions. Especially in family matters such as marriage or divorce, minority family members may look for alternative options outside of the state, concluding religious marriages or divorces.